HOSPITAL SUPERVISORY BOARD ROLE IN MEDICAL DISPUTE SETTLEMENT IN HOSPITAL (ANALYSIS TOWARD MECHANISM AND NORMATIVE OBSTACLES) - Nayla Alawiya; Aryuni Yuliantiningsih; Dessi Perdani Yuris Puspita Sari (Faculty of Law, Universitas Jenderal Soedirman, 2015)
Health services are not always able to deliver the results expected by the patient or the patient's family. The gap often makes the dissatisfaction that arises medical disputes, including disputes in the hospital. Law No. 44 of 2009 on the Hospital Board of Supervisors ordered the establishment of the Hospital that one role is to resolve disputes hospital. But government regulation of the Hospital Board of Supervisors recently issued in August 2013, and setting the Hospitals Act does not mention the prior regulations promulgated which raises normative barriers. The method used is normative. Results of this study is that the Supervisory Board has the task Central Hospital preparing procedures for handling complaints and mediation, while receiving the complaint and make efforts to resolve the dispute by way of mediation is the Supervisory Board Provincial Hospital. Hospital Board of Supervisors province can not perform tasks because the procedures for complaints and mediation has not been established by the Board of Supervisors Hospital Center. Law No. 44 Year 2009 has a setting that is not in sync with Act No. 39 of 2009 and Law No. 29 of 2004.Keywords: Supervisory Board Hospitals, normative barriers, dispute resolution, hospitals